Greenflation: Impacts on Public Policy and Economic Stability - Nurjaman, Daffa Syafiq (Department of Public Administration, 2024)
The study examined the phenomenon of greenflation and its implications for public policy and economic stability. Greenflataion refers to the rising costs of goods and services due to environmental policies and green transitions. This study employed a qualitative research design, analyzing secondary data from academic articles, policy reports, and economic analyses. Findings indicate that greenflation, while promoting environmental sustainability, presents challenges such as increased production costs, inflationary pressures, and social inequality. These outcomes necessitate comprehensive public policies to mitigate adverse economic impacts and ensure equitable green transitions. The study underscores the need for policy frameworks that balance environmental goals with economic stability and social equity.